Perceived effects of lead recycling to selected communities in Bulacan, Philippines - Visco, Emilia S. (Journal of Environmental Science and Management, 2013)
The province of Bulacan, Philippines is considered as the biggest producer of used lead acid battery (ULAB) in the country and in Southeast Asia. But with the boom of the ULAB industry, a continued concern on the industry's effect to human health and the environment intensifies. The study was conducted in two municipalities of Bulacan, Philippines to determine the perception of th respondents on the effects of lead recycling to their health and their community. These two areas are where ULAB industry is concentrated.